Midinfrared pulse generation by pumping in the normal-dispersion regime of a gas-filled hollow-core fiber - Hasan, Md Imran (2020)
We demonstrate, numerically, the generation of supercontinuum using a high-power ultrafast source at 1.06-μm wavelength and a nonlinear hollow-core fiber. We yield a system that is less sensitive to noise by pumping in the normal-dispersion regime, yet still achieves enhanced spectral broadening by exciting an optical soliton in the midinfrared region. The pump pulse goes through a series of nonlinear effects leading to a supercontinuum output that spans across the midinfrared, 0.5–4.2 μm